2019
DOI: 10.7752/jpes.2019.s3114
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A decrease in the frequency of physical activities is apparent in children and adolescents. This is partly due to their fondness for playing games on gadgets. If the decline in physical activity continues, it is feared that it may indirectly increase the prevalence of metabolic diseases, such as obesity, heart disease, and diabetes mellitus. One of the newest innovations to make exercise easier is video game-based exercises (exergaming). Via exergaming, exercises can be done while sitting down (only the upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Therefore, eight RCT reports were finally included to evaluate the effect of AVGs on physical activity among overweight and obese college students. The publication dates of these eight articles range from 2007 ( 47 ) to 2019 ( 48 ) and include one from Indonesia ( 48 ), one from Canada ( 47 ), two from Brazil ( 49 , 50 ), and the rest from the United States.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, eight RCT reports were finally included to evaluate the effect of AVGs on physical activity among overweight and obese college students. The publication dates of these eight articles range from 2007 ( 47 ) to 2019 ( 48 ) and include one from Indonesia ( 48 ), one from Canada ( 47 ), two from Brazil ( 49 , 50 ), and the rest from the United States.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 demonstrates several underlying components of the intervention characteristics in the included studies, mainly including the following. Intervention type: Two studies employed AVGs in combination with other devices (bicycles and mini-trampolines) ( 47 , 50 ).The remaining six utilised AVGs directly as the intervention ( 48 , 49 , 51–54 ). Intervention duration: A study did not specify the duration, only on two different days ( 53 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In his research, Zhao et al (2021) stated that exercises performed for 4 weeks did not affect the concentration of basal blood lactate. Rahayu et al (2019) in his study reported that there was a significant difference in heart rate recovery between 60 and 90 minutes after exercise. Therefore, how the fundamental impact of exercise on blood MDA and lactate levels remains controversial.…”
Section: Introductionmentioning
confidence: 92%